TRIM67 Suppresses TNFalpha-Triggered NF-kB Activation by Competitively Binding Beta-TrCP to IkBa - Fan, Wenchun; Liu, Xueyan; Zhang, Jinyan; Qin, Liuxing; Du, Jian; Li, Xiangmin; Qian, Suhong; Chen, Huanchun; Qian, Ping (Frontiers in Immunology, 2022)
The transcription factor NF-κB plays an important role in modulation of inflammatory pathways, which are associated with inflammatory diseases, neurodegeneration, apoptosis, immune responses, and cancer. Increasing evidence indicates that TRIM proteins are crucial role in the regulation of NF-κB signaling pathways. In this study, we identified TRIM67 as a negative regulator of TNFα-triggered NF-κB activation. Ectopic expression of TRIM67 significantly represses TNFα-induced NF-κB activation and the expression of pro-inflammatory cytokines TNFα and IL-6. In contrast, Trim67 depletion promotes TNFα-induced expression of TNFα, IL-6, and Mcp-1 in primary mouse embryonic fibroblasts. Mechanistically, we found that TRIM67 competitively binding β-transducin repeat-containing protein (β-TrCP) to IκBα results inhibition of β-TrCP-mediated degradation of IκBα, which finally caused inhibition of TNFα-triggered NF-κB activation. In summary, our findings revealed that TRIM67 function as a novel negative regulator of NF-κB signaling pathway, implying TRIM67 might exert an important role in regulation of inflammation disease and pathogen infection caused inflammation.